A double-shell ZIF-8 derived nitrogen and oxygen co-doped carbon nanoparticle and its preparation method and application

By preparing bi-shelled ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles, the problems of low Coulomb efficiency and volume expansion caused by Na dendrites in sodium ion batteries are solved, and uniform deposition of sodium and efficient cycling stability of the battery are achieved. sex.

CN116177534BActive Publication Date: 2025-02-14NEW MATERIAL INST OF SHANDONG ACADEMY OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310280836.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-02-14
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

The prior art In sodium ion batteries, the formation and growth of Na dendrites lead to low Coulomb efficiency, and the sodium ion batteries have poor circulation performance due to volume expansion during application, and even safety problems exist.

Method used

By preparing bihulled ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles, changing the specific surface area of ​​nitrogen-oxygen co-doped carbon nanomaterials, reducing local current density, providing abundant sites for uniform deposition of sodium, and through double- Volume changes during the buffer cycle of shell structure.

Benefits of technology

The uniform deposition of sodium in sodium ion batteries is achieved, the deposition point is reduced, the Coulomb efficiency and cycling stability are improved, and the performance attenuation and safety problems caused by volume expansion are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116177534B_ABST
    Figure CN116177534B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing nitrogen-oxygen co-doped carbon nanoparticles derived from double-shell ZIF-8, the method comprising: synthesizing ZIF-8, surface-modifying PVP of ZIF-8, etching of tannic acid, and high-temperature calcination. The NO-C material prepared by the present invention provides "sodium-loving" sites through uniformly distributed nitrogen-oxygen functional groups, effectively reducing the deposition sites. At the same time, the large specific surface area of ​​the NO-C material can effectively reduce the local current density and provide abundant sites for the uniform deposition of sodium. In addition, the double-shell structure of NO-C can effectively buffer the volume change during the cycle, so that it has the advantages of high stability and long-term reuse.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry and new energy materials, and specifically relates to nitrogen-oxygen co-doped carbon nanoparticles derived from double-shell ZIF-8 and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Metallic sodium is considered to be an excellent alternative to lithium-ion batteries due to its high natural reserves, low cost, and similar physical and chemical properties to metallic lithium. At the same time, metallic sodium is also regarded as an ideal candidate anode material due to its high theoretical capacity and low redox potential. However, during the continuous electroplating / stripping of sodium, the formation and growth of Na dendrites lead to problems such as low Coulombic efficiency, which seriously limits the development of sodium-ion batteries.

[0004] In order to solve this problem, scientists have explored many methods and strategies, such as: (1) optimizing the formulation of liquid electrolytes by changing the solvent of the electrolyte or adding additives to form a uniform and stable solid electrolyte interface phase; (2) constructing an artificial solid electrolyte interface phase on the sodium surface to passivate the interfacial reaction; (3) replacing liquid electrolytes with solid electrolytes to avoid the side reaction between metallic sodium and electrolytes, and to a certain extent inhibiting the growth of Na dendrites; (4) designing various skeletons for "hostless" Na metal anodes to control the sodium deposition behavior and achieve uniform Na nucleation. Among the above methods, the application of carbon-based materials is an effective method to inhibit the growth of dendrites during the sodium electroplating / stripping process, and the introduction of heteroatoms can provide a large number of "sodium-loving" sites, reduce the Na nucleation overpotential, and regulate the Na deposition behavior.

[0005] However, the specific surface area of ​​carbon-based materials will affect the richness of "sodium-loving" sites. A larger specific surface area can expose more "sodium-loving" sites, so how to prepare carbon-based materials with a larger specific surface area and more "sodium-loving" sites becomes a challenge. In addition, sodium-ion batteries often have poor cycle performance and even safety issues during use due to volume expansion, so how to construct the buffer structure of carbon-based materials has also become a key technical issue. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a double-shell ZIF-8 derived nitrogen-oxygen co-doped carbon nanoparticle and a preparation method and application thereof. By changing the specific surface area of ​​nitrogen-oxygen co-doped carbon nanomaterials (NO-C), the local current density can be effectively reduced, providing abundant sites for the uniform deposition of sodium. At the same time, the double-shell structure of the NO-C material can effectively buffer the volume change during the cycle, so that it has the advantages of high stability and long-term repeated use.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] The first aspect of the present invention provides a method for preparing double-shell ZIF-8 derived nitrogen-oxygen co-doped carbon nanoparticles, the method comprising:

[0009] S1. Dissolve zinc acetate and 2-methylimidazole in a methanol solution, stir evenly, and let the mixture stand at room temperature for a period of time to obtain ZIF-8 crystals. The ZIF-8 crystals are washed, centrifuged, and dried to obtain ZIF-8 powder;

[0010] S2. ZIF-8 powder and polyvinyl pyrrolidone (PVP) were added to an ethanol solution, stirred for a period of time, filtered, washed, centrifuged, and dried to obtain PVP surface-modified ZIF-8 particles (PVP@ZIF-8);

[0011] S3. The PVP surface-modified ZIF-8 particles are dispersed in an aqueous solution of tannic acid (TA), and the particles are etched to obtain double-shell ZIF-8 particles; the concentration of the tannic acid is 2 g / L to 10 g / L; the etching time is 5 min to 30 min;

[0012] S4. The double-shell ZIF-8 particles are calcined at high temperature in an inert gas environment, the calcined particles are immersed in a concentrated hydrochloric acid solution, and then dried to obtain double-shell ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles.

[0013] The second aspect of the present invention provides double-shell ZIF-8-derived nitrogen and oxygen co-doped carbon nanoparticles prepared by the above preparation method.

[0014] The third aspect of the present invention is the use of the above-mentioned double-shell ZIF-8 derived nitrogen and oxygen co-doped carbon nanoparticles in sodium ion batteries.

[0015] A fourth aspect of the present invention provides a negative electrode material for a sodium ion battery, wherein the negative electrode material comprises the nitrogen-oxygen co-doped carbon nanoparticles derived from the double-shell ZIF-8.

[0016] The beneficial effects of the present invention are:

[0017] (1) The NO-C material prepared by the present invention provides "sodium-loving" sites through uniformly distributed nitrogen and oxygen functional groups, effectively reducing the deposition sites. At the same time, the large specific surface area of ​​the NO-C material can effectively reduce the local current density and provide abundant sites for the uniform deposition of sodium. In addition, the double-shell structure of NO-C can effectively buffer the volume change during the cycle, making it have the advantages of high stability and long-term reuse.

[0018] (2) When the capacity is 1 mA·h·cm -2 When 0.5 mA·cm -2 The coulombic efficiency of the NO-C electrode remained at about 99.8% for 1100 cycles at a voltage overpotential of 8 mV. In addition, the NO-C / Na symmetric battery exhibited a high coulombic efficiency at 2 mA cm -2 It exhibits a stable and small polarization voltage of about 35 mV after 800 cycles.

[0019] (3) The operation method of the present invention is simple, low-cost, universal, and easy to scale up for production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] Figure 1 This is a SEM photo of the double-shell NO-C material prepared in Example 1 of the present invention;

[0022] Figure 2 This is a TEM photo of the double-shell NO-C material prepared in Example 1 of the present invention;

[0023] Figure 3 This is the XRD spectrum of the double-shell NO-C material prepared in Example 1 of the present invention;

[0024] Figure 4 This is the N2 adsorption-desorption curve of the double-shell NO-C material prepared in Example 1 of the present invention;

[0025] Figure 5 This is a diagram showing the nucleation point test results of the double-shell NO-C material and bare copper prepared in Example 1 of the present invention;

[0026] Figure 6 The voltage-capacity curve test result diagram of the double-shell NO-C material and bare copper prepared in Example 1 of the present invention; DETAILED DESCRIPTION

[0027] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0028] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0029] A first typical embodiment of the present invention provides a method for preparing double-shell ZIF-8 derived nitrogen-oxygen co-doped carbon nanoparticles, the method comprising:

[0030] S1. Dissolve zinc acetate and 2-methylimidazole in a methanol solution, stir evenly, and let the mixture stand at room temperature for a period of time to obtain ZIF-8 crystals. The ZIF-8 crystals are washed, centrifuged, and dried to obtain ZIF-8 powder;

[0031] S2. ZIF-8 powder and polyvinyl pyrrolidone (PVP) were added to an ethanol solution, stirred for a period of time, filtered, washed, centrifuged, and dried to obtain PVP surface-modified ZIF-8 particles (PVP@ZIF-8);

[0032] S3. The PVP surface-modified ZIF-8 particles are dispersed in an aqueous solution of tannic acid (TA), and the particles are etched to obtain double-shell ZIF-8 particles; the concentration of the tannic acid is 2 g / L to 10 g / L; the etching time is 5 min to 30 min;

[0033] S4. The double-shell ZIF-8 particles are calcined at high temperature in an inert gas environment, the calcined particles are immersed in a concentrated hydrochloric acid solution, and then dried to obtain double-shell ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles.

[0034] In one or more embodiments, the mass ratio of zinc acetate to 2-methylimidazole in step S1 is 0.3 to 1:1, preferably 0.6:1.

[0035] In one or more embodiments, the amount of methanol added in step S1 is 150 to 200 times the mass of zinc acetate, preferably 180 times.

[0036] In one or more embodiments, the standing time in step S1 is 20 to 30 hours, preferably 24 hours.

[0037] In one or more embodiments, the washing method in step S1 is to wash by centrifugation with excess ethanol for 3 to 5 times.

[0038] In one or more embodiments, the centrifugal speed in step S1 is 2000-5000 rpm, and the time is 3-10 min. Preferably, the speed is 3000 rpm, and the time is 5 min.

[0039] In one or more embodiments, the drying temperature in step S1 is 80-120°C, and optimally 100°C.

[0040] In one or more embodiments, the mass ratio of PVP to ZIF-8 powder in step S2 is 10 to 40:1, preferably 30:1.

[0041] In one or more embodiments, the amount of ethanol in step S2 is 100 to 150 times the mass of PVP, preferably 120 times.

[0042] In one or more embodiments, the stirring time in step S2 is 10 to 15 hours, preferably 12 hours.

[0043] In one or more embodiments, the specific method of washing in step S2 is: washing with ethanol for 3 to 5 times.

[0044] In one or more embodiments, the centrifugal speed in step S2 is 2000-5000 rpm, and the time is 3-10 min, and the optimal speed is 3000 rpm and the time is 5 min.

[0045] In one or more embodiments, the drying temperature in step S2 is 80-120°C, and optimally 100°C.

[0046] In one or more embodiments, in step S3, the PVP surface-modified ZIF-8 particles are dispersed into an aqueous solution of tannic acid (TA) by ultrasound, and the ultrasound time is 15 to 60 minutes, preferably 30 minutes.

[0047] In one or more embodiments, the mass ratio of the PVP surface-modified ZIF-8 particles to tannic acid in step S3 is 0.2 to 0.8:1, preferably 0.5:1.

[0048] The amount of tannic acid added and the etching time will affect the degree of tannic acid etching of ZIF-8, so the concentration of tannic acid and the etching time need to be controlled during the reaction.

[0049] In one or more embodiments, the inert gas in step S4 is nitrogen or argon.

[0050] In one or more embodiments, the high temperature calcination temperature in step S4 is 700-1000° C., preferably 900° C.; the calcination time is 2-5 hours, preferably 3 hours.

[0051] In one or more embodiments, the concentration of the concentrated hydrochloric acid is 0.8 to 1.2 mmol / L, preferably 1 mmol / L; the zinc atoms in ZIF-8 can be removed by high-temperature calcination and soaking in concentrated hydrochloric acid.

[0052] The process of forming double-shell ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles is mainly divided into four stages: synthesizing ZIF-8, modifying the surface of ZIF-8 with PVP, etching with tannic acid, and high-temperature calcination.

[0053] Synthesis of ZIF-8: Zinc acetate and 2-methylimidazole are coordinated to form the metal organic framework ZIF-8;

[0054] PVP modified on the surface of ZIF-8: Since the zinc on the surface of ZIF-8 can coordinate with the C=O functional group in PVP, a PVP@Zn layer is formed on the surface of ZIF-8;

[0055] Etching of tannic acid: Tannic acid, as an organic weak acid, can provide protons in aqueous solution, thereby destroying the coordination bonds between metal ions and ligands in metal organic frameworks (MOFs), leading to the decomposition of the MOFs skeleton. However, tannic acid has excellent adhesion properties. Tannic acid adsorbed on the surface of MOFs will cover MOFs, block the channels of MOFs, and prevent proton etching, which is equivalent to forming a protective film on the surface of MOFs. However, due to the large molecular size of tannic acid, it is difficult to diffuse inside MOFs. Therefore, tannic acid can only form a protective layer on the surface of MOFs. The internal MOFs structure will be destroyed due to the protons provided by tannic acid. Therefore, the etching process of tannic acid starts from the inside of MOFs. In order to retain the double-shell structure, the concentration of tannic acid and the etching time are strictly controlled. At the same time, by controlling the concentration of tannic acid and the etching time, the thickness of the shell, the presence of a core, and the size of the core can be controlled.

[0056] In order to form the final double-shell structure, the process of ZIF-8 surface modification with PVP must be carried out before tannic acid etching, otherwise PVP will be tightly attached to the surface of the single-shell MOFs formed after tannic acid etching, and no new shell structure will be generated.

[0057] High-temperature calcination: The zinc atoms in ZIF-8 can be removed by high-temperature calcination and soaking in concentrated hydrochloric acid, and double-shell ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles are obtained after drying.

[0058] A second typical embodiment of the present invention provides double-shelled ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles prepared by the above preparation method.

[0059] A third typical embodiment of the present invention provides the use of the above-mentioned double-shell ZIF-8 derived nitrogen and oxygen co-doped carbon nanoparticles in sodium ion batteries.

[0060] A fourth typical embodiment of the present invention provides a negative electrode material for a sodium ion battery, wherein the negative electrode material comprises the nitrogen-oxygen co-doped carbon nanoparticles derived from the double-shell ZIF-8.

[0061] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0062] Example 1

[0063] Preparation of double-shelled ZIF-8 derived nitrogen and oxygen co-doped carbon nanoparticles:

[0064] S1. 1.75 g of zinc acetate and 2.63 g of 2-methylimidazole were dissolved in 400 mL of methanol solution, stirred evenly, and the mixture was allowed to stand at room temperature for 24 h to obtain ZIF-8 crystals. The ZIF-8 crystals were washed with ethanol three times, centrifuged at a speed of 3000 rpm for 5 min, and dried at 100 ° C to obtain ZIF-8 powder;

[0065] S2. 0.03 g ZIF-8 powder and 1 g polyvinyl pyrrolidone (PVP) were added to 150 mL ethanol solution, stirred for 12 h, filtered, washed with anhydrous ethanol for 3 to 5 times, centrifuged at 3000 rpm for 5 min, and dried at 100 ° C to obtain PVP surface-modified ZIF-8 particles (PVP@ZIF-8);

[0066] S3. 0.08 g of PVP surface-modified ZIF-8 particles were dispersed in an aqueous solution of tannic acid (TA) at a concentration of 2 g / L, stirred and etched for 30 min to obtain double-shell ZIF-8 particles;

[0067] S4. The double-shell ZIF-8 particles were calcined at 900°C for 3 h under nitrogen conditions, and the calcined particles were immersed in a 1 mmol / L concentrated hydrochloric acid solution. After drying, double-shell ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles were obtained.

[0068] The double-shelled ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles prepared in this example were characterized. Figure 1 This is a SEM photo; Figure 2 For TEM images, Figure 2 The inner and outer shells of the double-hull structure can be clearly seen; Figure 3 is the XRD spectrum, Figure 3 The broad peak at 23° observed in can be attributed to the (002) crystal plane of graphite structure; Figure 4 is the BET nitrogen adsorption curve. Figure 4 It can be seen that there are obvious micropores and mesopores in the material.

[0069] Example 2 (Changing the concentration of tannic acid and etching time)

[0070] S1. 1.75 g of zinc acetate and 2.63 g of 2-methylimidazole were dissolved in 400 mL of methanol solution, stirred evenly, and the mixture was allowed to stand at room temperature for 24 h to obtain ZIF-8 crystals. The ZIF-8 crystals were washed with ethanol three times, centrifuged at a speed of 3000 rpm for 5 min, and dried at 100 ° C to obtain ZIF-8 powder;

[0071] S2. 0.03 g ZIF-8 powder and 1 g polyvinyl pyrrolidone (PVP) were added to 150 mL ethanol solution, stirred for 12 h, filtered, washed with anhydrous ethanol for 3 to 5 times, centrifuged at 3000 rpm for 5 min, and dried at 100 ° C to obtain PVP surface-modified ZIF-8 particles (PVP@ZIF-8);

[0072] S3. 0.08 g of PVP surface-modified ZIF-8 particles were dispersed in an aqueous solution of tannic acid (TA) at a concentration of 5 g / L, stirred and etched for 60 min to obtain double-shell ZIF-8 particles;

[0073] S4. The double-shell ZIF-8 particles were calcined at 900°C for 3 h under nitrogen conditions, and the calcined particles were immersed in a 1 mmol / L concentrated hydrochloric acid solution. After drying, double-shell ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles were obtained.

[0074] Comparative Example 1

[0075] Compared with Example 1, PVP was not added to S2, and the other experimental steps were the same as those in Example 1.

[0076] Comparative Example 2

[0077] Compared with Example 1, tannic acid is not added in S3 for etching, and other experimental steps are the same as those in Example 1.

[0078] Compared with Example 1, Comparative Example 1 obtains a single shell structure, while Comparative Example 2 cannot obtain a shell structure. The shell structure can effectively buffer the volume change of the sodium ion battery during the cycle use, and reduce the performance degradation caused by volume expansion. Comparative Example 2 cannot form a shell structure, so it cannot form a buffer structure, causing the material performance to decay severely during use. Although Comparative Example 1 can form a single shell structure, the buffering effect is significantly lower than that of the double-layer structure, proving that more shells have a stronger buffering effect during volume expansion and contraction.

[0079] Example 3

[0080] The nitrogen-oxygen co-doped carbon nanoparticles derived from the double-shell ZIF-8 prepared in Example 1 are used as the negative electrode material for sodium ion batteries.

[0081] 0.8g of double-shelled ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles and 0.1g of sodium alginate were added to a mortar and ground thoroughly. 5mL of deionized water was added to grind into a uniform slurry, and the obtained slurry was coated on a bright copper foil and dried to obtain the negative electrode. The electrochemical performance was characterized by constant current sodium plating / dissolution process. The electrolyte was 1M sodium hexafluorophosphate / diethylene glycol dimethyl ether, the positive electrode was sodium, and glass microfiber was used as a separator.

[0082] like Figure 5 As shown in the figure, the nucleation overpotential test of the double-shell NO-C material and bare copper obtained in Example 3 is shown. It can be seen from the figure that a sharp peak is observed in the initial Na deposition phase on the bare Cu, and the recorded voltage value is 14mV. The nucleation overpotential of the double-shell NO-C is only 8mV, which is much lower than that of bare Cu, indicating that the double-shell NO-C can effectively reduce the Na nucleation resistance.

[0083] like Figure 6 As shown in the figure, the coulombic efficiency test of the double-shell NO-C material and bare copper obtained in Example 3 is as shown in the figure. At a current density of 0.5 mA·cm -2 , capacity is 1mA·h·cm -2 The double-shell NO-C electrode exhibits an extremely high average Coulombic efficiency of 99.8% with a minimal overpotential of about 8 mV over 1100 cycles. In contrast, bare Cu exhibits a huge Coulombic efficiency change after only 130 cycles, a typical sign of repeated growth / dissolution of Na dendrites during cycling.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing double-shell ZIF-8 derived nitrogen-oxygen co-doped carbon nanoparticles, characterized in that: The method comprises: S1. Dissolve zinc acetate and 2-methylimidazole in a methanol solution, stir evenly, and let the mixture stand at room temperature for a period of time to obtain ZIF-8 crystals. The ZIF-8 crystals are washed, centrifuged, and dried to obtain ZIF-8 powder; S2. ZIF-8 powder and polyvinyl pyrrolidone were added to an ethanol solution, stirred for a period of time, filtered, washed, centrifuged, and dried to obtain PVP surface-modified ZIF-8 particles; S3. The ZIF-8 particles modified with PVP are dispersed in an aqueous solution of tannic acid, stirred and etched to obtain ZIF-8 particles with a double-shell structure; the concentration of the tannic acid is 2 g / L to 10 g / L; the etching time is 5 min to 30 min; S4. The double-shell ZIF-8 particles are calcined at high temperature in an inert gas environment, the calcined particles are immersed in a concentrated hydrochloric acid solution, and dried to obtain double-shell ZIF-8-derived nitrogen-oxygen co-doped carbon nanoparticles; In step S4, the inert gas is nitrogen or argon; The high temperature calcination temperature in step S4 is 700-1000° C., and the calcination time is 2-5 hours.

2. The preparation method according to claim 1, characterized in that In step S1, the mass ratio of zinc acetate to 2-methylimidazole is 0.3-1:1; Alternatively, the standing time in step S1 is 20 to 30 h.

3. The preparation method according to claim 1, characterized in that: The mass ratio of zinc acetate to 2-methylimidazole in step S1 is 0.6:

1.

4. The preparation method according to claim 1, characterized in that: The standing time in step S1 is 24 hours.

5. The preparation method according to claim 1, characterized in that: The washing method in step S1 is to wash by centrifugation with excess ethanol for 3 to 5 times; Or, in step S1, the centrifugal speed is 2000-5000 rpm, and the time is 3-10 min; Alternatively, the drying temperature in step S1 is 80-120°C.

6. The preparation method according to claim 1, characterized in that: The drying temperature in step S1 is 100°C.

7. The preparation method according to claim 1, characterized in that: In step S1, the centrifugal speed is 3000 rpm and the time is 5 min.

8. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of PVP to ZIF-8 powder is 10-40:1; Alternatively, the amount of ethanol in step S2 is 100 to 150 times the mass of PVP.

9. The preparation method according to claim 1, characterized in that: The mass ratio of PVP to ZIF-8 powder in step S2 is 30:

1.

10. The preparation method according to claim 1, characterized in that: The amount of ethanol in step S2 is 120 times the mass of PVP.

11. The preparation method according to claim 1, characterized in that: The stirring time in step S2 is 10 to 15 hours; The specific method of washing in step S2 is: washing with ethanol 3 to 5 times; Or, in step S2, the centrifugal speed is 2000-5000 rpm, and the time is 3-10 min; Alternatively, the drying temperature in step S2 is 80-120°C.

12. The preparation method according to claim 1, characterized in that: In step S2, the centrifugal speed is 3000 rpm and the time is 5 min.

13. The preparation method according to claim 1, characterized in that: The drying temperature in step S2 is 100°C.

14. The preparation method according to claim 1, characterized in that: The stirring time in step S2 is 12 hours.

15. The preparation method according to claim 1, characterized in that: In step S3, the PVP surface-modified ZIF-8 particles are dispersed into an aqueous solution of tannic acid by ultrasound, and the ultrasound time is 15 to 60 min; Alternatively, in step S3, the mass ratio of the PVP surface-modified ZIF-8 particles to tannic acid is 0.2-0.8:

1.

16. The preparation method according to claim 1, characterized in that: In the step S3, the PVP surface-modified ZIF-8 particles are dispersed into an aqueous solution of tannic acid by ultrasound, and the ultrasound time is 30 min.

17. The preparation method according to claim 1, characterized in that: In the step S3, the mass ratio of the ZIF-8 particles modified with PVP surface to tannic acid is 0.5:

1.

18. The preparation method according to claim 1, characterized in that: The temperature of high temperature calcination in step S4 is 900°C; Or, the concentration of the concentrated hydrochloric acid is 0.8~1.2 mmol / L.

19. The preparation method according to claim 1, characterized in that: The high temperature calcination time in step S4 is 3 hours.

20. The preparation method according to claim 1, characterized in that: The concentration of the concentrated hydrochloric acid is 1 mmol / L.

21. Double-shelled ZIF-8-derived nitrogen and oxygen co-doped carbon nanoparticles prepared by the preparation method according to any one of claims 1 to 20.

22. Use of double-shelled ZIF-8 derived nitrogen and oxygen co-doped carbon nanoparticles prepared by the preparation method according to any one of claims 1 to 20 and / or double-shelled ZIF-8 derived nitrogen and oxygen co-doped carbon nanoparticles according to claim 21 in sodium ion batteries.

23. A negative electrode material for a sodium ion battery, the negative electrode material comprising double-shelled ZIF-8 derived nitrogen and oxygen co-doped carbon nanoparticles prepared by the preparation method according to any one of claims 1 to 20 and / or double-shelled ZIF-8 derived nitrogen and oxygen co-doped carbon nanoparticles according to claim 21.

Citation Information

Patent Citations

  • Preparation method and application of transition metal-based double-shell carbon nanobox

    CN115149011A